HUBUNGAN PENGETAHUAN GIZI DAN POLA MAKAN PADA REMAJA PUTRI DENGAN KEJADIAN ANEMIA DI SMP NEGERI 2 KOTAPINANG KABUPATEN LABUHAN BATU SELATAN TAHUN 2014 - Damayani .; Etti Sudaryati; Muhammad Arifin Siregar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Anemia is one of the health problems that continue to be the government’s attention. Among the various types of anemia, anemia in adolescent girls is the biggest anemia problem in society. This happenes because the girls undergo the process ef menstruation and a diet that causes a lack of nutrition. This research is descriptive survey that aim to know nutrition knowledge, diet, and anemia in SMP Negeri 2 Kotapinang South Labuhan Batu district. The population in this study were students of class seventh, eight, nineth in SMP Negeri 2 Kotapinang many as 567 people. The sample was selected a part of the population of 88 people. Collecting data using the nutrition knowledge questionnaire. Data form the diet using food frequency and 24-hours food recall. The research resultshowed that nutrition knowledge of students is good enough showed by 52,3%. The students didn’t consume staple food, fishes, vegetable, and fruit everyday showed by consume frequency is 71,6% is seldom. Anemia in student of SMP Negeri 2 Kotapinang is high showed by 71,4% anemia. Based on the research, results, expected the importance of improving information for student of SMP Negeri 2 Kotapinang about the importance of consume foods the certain mani Fe, vitamin and mineral as source of food which is able to prevent anemia needed menu cycle so that the food more regular by frequency, type and amount side. Keywords : knowledge of nutrition, diet, anemia